Prodrugs for Nitroreductase Based Cancer Therapy-5: Development of Trinitroaniline Prodrugs/Ssap-NtrB Combinations for Liver Cancer Using Intracellular and Extracellular Conditions - Hacioglu, Nelin; Gungor, Tugba; Tokay, Esra; Gulhan, Unzile Guven; Celik, Ayhan; Ay, Mehmet; Kockar, Feray (Wiley-V C H Verlag Gmbh, 2021)
In this study, a series of trinitroaniline derivatives (TNA1-8) were synthesized and investigated as potential antitumor agents for enzyme-prodrug therapy. Enzymatic efficiency of Ssap-NtrB on prodrug candidates was determined with HPLC analysis and kinetic studies. The anti-proliferative properties of compounds were determined against four cancer cell lines (Hep3B, PC3, HT-29, and Saos-2) and a healthy cell line (HUVEC) via MTT assay. Intracellular and extracellular prodrug-enzyme treatments were carried out on Hep3B cells. Herewith, the expression of the Ssap-NtrB gene was confirmed with this study. IC50 values of piperidine and 1,3-cyclohexyl derivatives (TNA4 and TNA7) were identified as 1.724 nM and 1.640 nM at extracellular conditions. In intracellular conditions, it was determined as 0.293 mu M and 0.393 mu M, respectively. In summary, 2,4,6-trinitroaniline derivatives, especially compounds TNA4 and TNA7 might be used as prodrug candidates along with Ssap-NtrB for hepatocellular carcinoma therapy and the development of new prodrugs at cancer treatments.
Keywords: cytotoxicity; nitroreductase; prodrugs; Ssap-NtrB; Trinitroaniline